2020
DOI: 10.1177/0954405420949127
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the sensitivity of acoustic emission signal features to the variation of cutting parameters in milling aluminum alloys: Part A: frequency domain analysis

Abstract: It is known that adequate knowledge of the sensitivity of acoustic emission signal parameters to various experimental parameters is indispensable. According to the review of the literature, a lack of knowledge was noticeable concerning the behavior of acoustic emission parameters under a broad range of machining parameters. This becomes more visible in milling operations that include sophisticated chip formation morphology and significant interaction effects and directional pressures and forces. To remedy the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In the frequency domain, the conclusions revealed that peak amplitude and peak frequency entitled as the most sensitive factors to input catting parameters. They were not still satisfactorily governed by such parameters [44]. The negligible P-Value (<<0.05) of feed per tooth, cutting speed, coating material, and depth of cut when taking rms, std, energy and entropy throughout the wavelet transform analysis of decomposed AE detail signals of milling of Aluminium 7075 was observed and considered.…”
Section: Resultsmentioning
confidence: 98%
“…In the frequency domain, the conclusions revealed that peak amplitude and peak frequency entitled as the most sensitive factors to input catting parameters. They were not still satisfactorily governed by such parameters [44]. The negligible P-Value (<<0.05) of feed per tooth, cutting speed, coating material, and depth of cut when taking rms, std, energy and entropy throughout the wavelet transform analysis of decomposed AE detail signals of milling of Aluminium 7075 was observed and considered.…”
Section: Resultsmentioning
confidence: 98%